Acute Kidney Injury as Predictor of Major Adverse Cardiac Event (MACE) in 3 Months after Admission of Acute Heart Failure Patients in Haji Adam Malik General Hospital Medan - Chan, Muhammad Ikhsan; Andra, Cut Aryfa; Raynaldo, Abdul Halim; Hasan, Harris; Sarastri, Yuke; Sitepu, Andika (Universitas Airlangga, 2024)
Highlights: 1. This study provides novel evidence that acute kidney injury (AKI) is a strong predictor of major adverse cardiovascular events (MACE) in patients with acute heart failure, highlighting the critical need for early detection and intervention to improve outcomes. 2. This research underscores the importance of incorporating kidney function assessment into the comprehensive management of acute heart failure patients. - Background: Acute heart failure is a condition with high morbidity and mortality. Decreased renal function after hospitalization is a predictor of longer hospitalization and increased mortality. Patients with acute renal failure, especially injury or failure grade, have a worse long-term prognosis compared to patients without acute renal failure, which will lead to MACE. Major adverse cardiovascular events are a combination of non-fatal stroke, non-fatal myocardial infarction, or cardiovascular death. Material and Methods: This study was a retrospective cohort study of 159 patients with acute heart failure at HAM General Hospital from April 1, 2023 to December 31, 2023. Electrocardiographic, laboratory, and echocardiographic data were collected. Patients were categorized according to RIFLE classification and monitored to see MACE in the samples. Bivariate tests were performed to see the correlation between samples. Furthermore, Kaplan-Meier curves were analyzed to see the survival rate. Results: Total subjects were 159 patients consisting of 98 acute heart failure patients with AKI and 61 heart failure patients without AKI. There was a correlation between heart failure patients who developed acute renal failure and the number of days of hospitalization (p = 0.000), in hospital mortality (p = 0.002), rehospitalization in less than 3 months (p = 0.000), and mortality in less than 3 months (p = 0.001). Conclusion: Acute kidney injury has a correlation with MACE so that it can be a predictor of major cardiovascular events in patients with acute heart failure.